2001
DOI: 10.1089/089277901300189385
|View full text |Cite
|
Sign up to set email alerts
|

Transitional-Cell Carcinoma of the Renal Pelvis: Ureteroscopic and Percutaneous Approach

Abstract: There are a variety of publications advocating the ureteroscopic or the percutaneous approach for the treatment of transitional cell carcinoma of the renal pelvis. The diagnostic tool of choice for the upper urinary tract and collecting system is the flexible ureteroscope. One of the major concerns about ureteroscopic management of renal disease initially was the lack of flexibility of the instruments and therefore the inability to deal with demanding sites. The advent of new ureteroscopic techniques, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 44 publications
0
40
0
2
Order By: Relevance
“…Often, repeated and frequent endoscopic surveillance is appropriate in this population. Endoscopic therapy offers the advantages of minimally invasive surgery, and in highly selected patients, it may provide results equivalent to radical extirpative surgery [60,61].…”
Section: Ureteroscopymentioning
confidence: 99%
“…Often, repeated and frequent endoscopic surveillance is appropriate in this population. Endoscopic therapy offers the advantages of minimally invasive surgery, and in highly selected patients, it may provide results equivalent to radical extirpative surgery [60,61].…”
Section: Ureteroscopymentioning
confidence: 99%
“…21,[47][48][49] In review of several large series, recurrence rates for grade 1 (5-20%) 24,47-50 and grade 2 disease (6-33%) 24,47-51 have been reported as significantly lower than recurrence rates for grade 3 disease (31-60%). 24,[47][48][49] In a large series of 62 patients with low-grade disease undergoing percutaneous resection followed by immediate Mitomycin C therapy and adjuvant Bacillus Calmette-Guérin (BCG) therapy, Montanari et al 52 observed no upper tract recurrences and only one bladder recurrence with a mean follow-up of 71 months. Jabbour et al 51 reviewed their experience in 24 patients with grade 2 disease and observed a 25% tumor recurrence rate with only one patient progressing to invasive disease with a mean follow-up of 48 months.…”
Section: Discussionmentioning
confidence: 99%
“…55 The incidence of blood loss varies among investigators and depends greatly on the size and extent of the treated lesion as well as ease of access, but transfusion rates up to 37% have been reported. 49 …”
Section: Benefits and Limitationsmentioning
confidence: 99%
“…La ablación endoscópica puede ser considerada en casos altamente seleccionados, como sería tumores unifocales, menores de 1-1.5 cm, de bajo grado y sin evidencia de lesión infiltrante en la urografía por tomografía computerizada multidetector, sin embargo, existe el riesgo de infraestadiaje de la enfermedad con este tipo de tratamiento (1,3). Es preferible el uso de ureteroscopio flexible frente al rígido, quedando el acceso percutáneo como una opción para los tumores localizados a nivel calicial a los cuales no se puede acceder mediante ureterorrenoscopia (21,22).…”
Section: La Urografía Por Resonancia Magnética (Rm) Está Indicada En unclassified